A robust nonlinear control strategy of a PV System connected to the three-phase grid based on backstepping and PSO technique - Salma Zouga; Mohamed Benchagra; Abdallah Ailane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This article presents a robust non-linear control technique of the three-phase photovoltaic system. The structure chosen for this PV system is that of two power converters and DC voltage intermediate bus. The two power converters are: the DC-DC converter and the three-phase inverter, which requires two main controllers. These controllers have three main objectives. The first objective is to impose the PV voltage generated by the photovoltaic panel, in order to follow a maximum reference voltage provided by the MPPT block. The second one is to maintain the DC link voltage to a constant value, in order to optimize the transfer of energy between the two power converters. The last objective is to inject a three-phase sinusoidal current into the grid, while respecting a unit power factor. With the intention to achieve these three objectives, we designed cascading nonlinear controllers by using the technique of non-linear backstepping control in the synthesis of these two controllers, based on the Lyapunov function, with regard to maximise the PVG output voltage, in order to have a unitary power factor at the grid side. In order to regulate DC-link voltage, we developed an integral proportional controller (PI) with parameters that are optimized by the Particle Swarm Optimization (PSO) method. The robustness of the controller designed approach is tested by a simulation in MATLAB/Simulink software, that improves the performances of each controller whatever conditions of climate.